2019
DOI: 10.1021/acs.energyfuels.9b00307
|View full text |Cite
|
Sign up to set email alerts
|

Acid Dicationic Ionic Liquids as Extractants for Extractive Desulfurization

Abstract: A series of imidazole- and pyridine-based dicationic ionic liquids (DILs) were synthesized and employed in extractive desulfurization (EDS) for the removal of sulfur compounds from commercial fluid catalytic cracking (FCC) gasoline. The influence parameters in the EDS process and regeneration of DILs are discussed. Under optimum operating conditions, the desulfurization efficiency can reach 79.72%. After five cycles, the sulfur content was reduced to less than 10 μg/g, and deep desulfurization was realized. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(18 citation statements)
references
References 50 publications
3
15
0
Order By: Relevance
“…Many ILs have been developed which are used as both the catalyst and extractant. Usually, the cation side of ILs influences the extraction ability of this material for DBT removal [38]. Therefore, the extraction ability of DILs was investigated.…”
Section: Catalytic Activity Of Catalystmentioning
confidence: 99%
See 1 more Smart Citation
“…Many ILs have been developed which are used as both the catalyst and extractant. Usually, the cation side of ILs influences the extraction ability of this material for DBT removal [38]. Therefore, the extraction ability of DILs was investigated.…”
Section: Catalytic Activity Of Catalystmentioning
confidence: 99%
“…In addition, through electrostatic interaction and hydrogen bonding, the double cation can be well connected with the anion, so as to improve the overall catalytic activity of the catalyst. Due to their unique properties, DILs have been successfully used and achieved ideal effects in esterification, supercapacitor, biodiesel catalysis and extractive desulfurization as eutectic solvents/catalysts, electrolyte additives, catalysts and extractant, respectively [35][36][37][38]. In our group's recent research results, a series of novel binuclear magnetic ionic liquids (MILs) [Cn(MIM)2]Cl2/mFeCl3 (n = 2, 4 or 6 and m = 1, 2 or 3) were synthesized and used as catalysts for the desulfurization with oxidant H2O2 and extractant acetonitrile [39].…”
Section: Introductionmentioning
confidence: 99%
“…The 1 H NMR data are shown in Figure . The chemical shift of ring protons in T (line a) were upfield than ring protons in TRIL (line b) because the average electron density of each ring carbon in PTSA was lower than that in T . It can be observed that the peak shape of the active hydrogen spectra changed significantly and the chemical shift of ring protons in TRIL moved into higher field after extraction (line c).…”
Section: Resultsmentioning
confidence: 99%
“…The results showed that due to the addition of solvent, the viscosity of the composite extractant was greatly reduced, the mass transfer process was enhanced, and a high extraction performance was achieved. Li et al 35 synthesized a series of imidazole- and pyridine-based binuclear ionic liquid extractants for extractive desulfurization of fuel oil. Due to the large cation volume of the dicationic ionic liquid, its cation has a large aromatic π electron density, which can effectively reduce the electrostatic force between the cation and anion, increase the π–π interaction between the cation and sulfide, and make it easier to extract sulfide from the oil phase.…”
Section: Introductionmentioning
confidence: 99%